2014
DOI: 10.1186/1752-4458-8-41
|View full text |Cite
|
Sign up to set email alerts
|

Social support moderates stress effects on depression

Abstract: This study examined the moderator effect of social support on the relationship between stress and depression of university students. A total of 632 undergraduate students completed the measures of perceived stress, perceived social support, and depression. Hierarchical regression analysis showed that social support moderated the association between stress and depression. Undergraduate students with high stress reported higher scores in depression than those with low stress with low social support level. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
169
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(197 citation statements)
references
References 46 publications
18
169
2
8
Order By: Relevance
“…Being able to turn to others and experience others as helpful is commonly regarded as a resource that buffers depression, anxiety and stress [7,116]. We were slightly surprised therefore that the correlations here were quite weak, although stronger for well-being.…”
Section: Compassion From Othersmentioning
confidence: 70%
See 2 more Smart Citations
“…Being able to turn to others and experience others as helpful is commonly regarded as a resource that buffers depression, anxiety and stress [7,116]. We were slightly surprised therefore that the correlations here were quite weak, although stronger for well-being.…”
Section: Compassion From Othersmentioning
confidence: 70%
“…Having access to caring and compassionate relationships buffers against the impact of negative life events on depression, and improves recovery trajectories, post-treatment functioning and relapse prevention (e.g., [8,34]). In a recent study of 632 students, Wang et al [116] found that social support significantly moderated the effect of stress on depression. Studies of compassion can therefore assess the degree to which individuals feel themselves contextualised in supportive environments where people have compassionate competencies.…”
Section: Compassion From Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the lack of an intimate, supportive relationship has been shown to be an antecedent to depression (Hirschfeld & Cross, 1983), while having more numerous and more supportive social resources can improve post-treatment functioning and prevent depressive relapse (Billings & Moos, 1985;George, Blazer, Hughes, & Fowler, 1989). Moreover, individuals who perceive higher levels of social support are less susceptible to the impact of stress on depression than those who perceive lower levels of support (Wang, Cai, Qian, & Peng, 2014).…”
Section: Fear Of Receiving Compassion and Depressionmentioning
confidence: 99%
“…[20] Accessibility of support in an ED worsened when the amount of patients increased and the duties of nurses expanded. [21] Social support has been investigated in relation to several clinical conditions like mental disorders, [22] cancer, [15] and heart disease, [3] and was found to be sufficient, but ED settings not been researched. Earlier study has shown associations between background factors such as marital status and education to social support.…”
Section: Introductionmentioning
confidence: 99%